Correction: Historical precipitation and flood damage in Japan: Functional data analysis and evaluation of models. - Atsushi Wakai; Yasuaki Hijioka; Masayuki Yokozawa; Manabu Watanabe; Gen Sakurai (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0318335.].